2016
DOI: 10.1038/srep34058
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functional nano silver: A novel disruptive and theranostic agent for pathogenic organisms in real-time

Abstract: The present study was aimed at evaluating the fluorescence property, sporicidal potency against Bacillus and Clostridium endospores, and surface disinfecting ability of biogenic nano silver. The nano silver was synthesized using an actinobacterial cell-filtrate. The fluorescence property as well as imaging facilitator potency of this nano silver was verified adopting spectrofluorometer along with fluorescent and confocal laser scanning microscope wherein strong emission and bright green fluorescence, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…As described earlier, larger surface area of silver nanoparticles are believed to be key player in interaction with bacterial cell wall and would have resulted in more antibacterial activity. Although mechanism of action of silver NPs on bacterial cell is debatable; however, assumed mechanism include (i) adherence of AgNPs with bacterial cell wall causing membrane lysis, ultimately releasing cellular contents leading to destruction of cell structure and death [89][90][91], (ii) interaction of Ag ions with free thiol groups (−SH) and disulfide bridges (-S-S-) of cellular enzymes and membrane of bacteria to downregulate or inactivate the cellular protein synthesis by interfering the translation [72,91,92], (iii) blocking DNA replication [93], and (iv) inhibition of signal transduction by dephosphorylation of peptide substrates on tyrosine residues (Figure 2) [91]. Furthermore, inhibitory effect of AgNPs varied for different bacterium, e.g., Gram-positive bacteria were more susceptible to silver nanoparticles as compared to Gram-negative one [84].…”
Section: Antibacterial Activity Of Mycosynthesized Nanoparticlesmentioning
confidence: 99%
“…As described earlier, larger surface area of silver nanoparticles are believed to be key player in interaction with bacterial cell wall and would have resulted in more antibacterial activity. Although mechanism of action of silver NPs on bacterial cell is debatable; however, assumed mechanism include (i) adherence of AgNPs with bacterial cell wall causing membrane lysis, ultimately releasing cellular contents leading to destruction of cell structure and death [89][90][91], (ii) interaction of Ag ions with free thiol groups (−SH) and disulfide bridges (-S-S-) of cellular enzymes and membrane of bacteria to downregulate or inactivate the cellular protein synthesis by interfering the translation [72,91,92], (iii) blocking DNA replication [93], and (iv) inhibition of signal transduction by dephosphorylation of peptide substrates on tyrosine residues (Figure 2) [91]. Furthermore, inhibitory effect of AgNPs varied for different bacterium, e.g., Gram-positive bacteria were more susceptible to silver nanoparticles as compared to Gram-negative one [84].…”
Section: Antibacterial Activity Of Mycosynthesized Nanoparticlesmentioning
confidence: 99%
“…Gopinath et al . found that biogenic AgNPs are effective against endospores of Bacillus and Clostridium species 31 . Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liu and co-authors have used gold nanoparticles for imaging (SERS, CT, and TPL imaging) and photothermal therapy in mouse models of sarcomas and shown that gold nanostars are more effective than gold nanoshells [88]. There are also reports on the theranostic application of Ag NPs or Pt NPs [89,90].…”
Section: Bioimaging and Molecular Diagnosismentioning
confidence: 99%